Pengaruh Dewan Komisaris Independen, Kepemilikan Institusional dan Corporate Social Responsibility terhadap Kinerja Keuangan - Amanda Maharani; Siti Khairani (Syntax Corporation Indonesia, 2025)
This study aims to examine the influence of the Independent Board of Commissioners, Institutional Ownership, and Corporate Social Responsibility on Financial Performance. The research focuses on manufacturing companies in the food and beverage sub-sector listed on the Indonesian Stock Exchange (IDX) during the 2019-2023 period. The sample was selected using purposive sampling, resulting in 26 companies as the research objects. Data analysis was conducted using multiple linear regression methods. The study results show that (1) The Independent board of commissioners has no significant impact on financial performance and shows a negative relationship. (2) Institutional ownership has a positive and significant effect on financial performance. Meanwhile, (3) Corporate Social Responsibility does not have a significant effect on financial performance and tends to exhibit a negative relationship.